Diferenças e continuidades na arqueologia e na genealogia de Foucault: entre 1966 e 1976 - Arantes de Souza, Lívia Francisco (2020)
This dissertation aims to study the relationship between Foucault's archaeological and genealogical researches taking into consideration Les mots et les choses archeology of human sciences; the debate raised by the publication of this book; Foucault's elaborations on genealogy and the history in Nietzsche's thoughts; Foucault's methodological approach in L'Ordre du discours, the summaries of the courses at the Collège de France of the first half of the 1970s and the Il faut défendre la société course. Our goal is to observe the introduction of new problems and concepts, conceptual changes, and how Foucault's attention moves towards addressing the relationship between discursive practices and practices of another nature. The hypothesis that conducts this research considers that, at the moment when Foucault marks the dispersed character of the genealogies of the early 1970s, he begins an investigation that touches the task of revising how the history of history is told, indicated in Les mots et les choses, but based on the conceptual redefinitions provided by the debate around the publication of book in 1966. Thus, we consider that Foucault's archaeological and genealogical researches are marked by complementary conceptual shifts and that the discussion about his methodological approaches gains in quality if we avoid using the framework of Foucault's philosophical trajectory in well-defined methodological phases.